Validation of reference genes for the normalization of RT-qPCR gene expression in Bacillus siamensis 1021 grown in different culture media - Nuwong, Warinya; Kittiwongwattana, Chokchai (My University, 2022)
Background and Objectives: House-keeping genes are generally selected as reference genes in gene expression analysis. However, some genes may not be stably expressed across all experimental conditions. Thus, this study aimed to validate seven house-keeping genes for gene expression analysis in Bacillus siamensis 1021. Materials and Methods: Strain 1021 was grown in potato dextrose broth, nutrient broth and mineral salt medium. Re-verse-transcription quantitative PCR was used to determine Cq values of seven reference genes including gyrA, gyrB, ssb and dnaB, rpsU, gat_Yqey and udp in these media. Expression stability of these genes was analyzed, using geNorm and Normfinder applications. The target gene ftsZ was used for assessment of the best candidate genes. Results: Based on geNorm and Normfinder, ssb was the most-stably expressed gene, while udp was the least-stably expressed gene. Pairwise variation indicated the combination of ssb, gyrA, gyrB and gatB_Yqey was suitable for the normalization of ftsZ expression. ftsZ expression in potato dextrose broth and mineral salt medium was higher than that in nutrient broth. In contrast, the normalization against udp resulted in an under-and overestimation of ftsZ expression in potato dextrose broth and mineral salt medium, respectively. Conclusion: The combination of ssb, gyrA, gyrB and gatB_Yqey was the best candidate for normalization of target gene expression in B. siamensis 1021 in these media. This study emphasized the significance of reference gene validation for gene expression analysis and provided a guideline for future gene expression studies in B. siamensis.
Keywords: Bacillus; Culture media; Gene expression; Reverse-transcription quantitative polymerase chain reaction